2013
DOI: 10.1073/pnas.1216351110
|View full text |Cite
|
Sign up to set email alerts
|

Leptin promotes K ATP channel trafficking by AMPK signaling in pancreatic β-cells

Abstract: Leptin is a pivotal regulator of energy and glucose homeostasis, and defects in leptin signaling result in obesity and diabetes. The ATP-sensitive potassium (K ATP ) channels couple glucose metabolism to insulin secretion in pancreatic β-cells. In this study, we provide evidence that leptin modulates pancreatic β-cell functions by promoting K ATP channel translocation to the plasma membrane via AMP-activated protein kinase (AMPK) signaling. K ATP channels were localized mostly to intracellular compartments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 39 publications
(49 reference statements)
9
106
0
Order By: Relevance
“…Leptin inhibits insulin secretion by increasing the cell-surface expression and the open probability of K ATP channels, resulting in a more hyperpolarized membrane potential (Holz et al, 2013). Leptin also induces an increased surface expression of Kv2.1 channels, leading to a rapid repolarization of membrane potential (Park et al, 2013b). These studies suggest that leptin exerts a coordinated trafficking regulation of K ATP and Kv2.1 channels to inhibit insulin secretion (Wu et al, 2015).…”
Section: Pharmacology Of K Atp Channels In Pancreatic Beta Cellsmentioning
confidence: 87%
See 1 more Smart Citation
“…Leptin inhibits insulin secretion by increasing the cell-surface expression and the open probability of K ATP channels, resulting in a more hyperpolarized membrane potential (Holz et al, 2013). Leptin also induces an increased surface expression of Kv2.1 channels, leading to a rapid repolarization of membrane potential (Park et al, 2013b). These studies suggest that leptin exerts a coordinated trafficking regulation of K ATP and Kv2.1 channels to inhibit insulin secretion (Wu et al, 2015).…”
Section: Pharmacology Of K Atp Channels In Pancreatic Beta Cellsmentioning
confidence: 87%
“…The mechanism by which leptin activates K ATP channels involves phosphatase and tensin homologe inhibition mediated by phosphoinositide 3 kinase. phosphatase and tensin homologe inhibition induces F-actin depolymerization and, consequently, K ATP channel opening (Park et al, 2013b;Wu et al, 2015).…”
Section: Endogenous Regulation Of K Atp Channels In the Beta Cellmentioning
confidence: 99%
“…Many proteins pass through early endosomes in the recycling process. K ATP channels likely follow this route, as evidenced by the partial colocalization of internalized Kir6.2 in pancreatic ␤-cells with the early endosome antigen 1 (EEA1) protein, which serves as a marker for this cellular compartment (632). The term early endosome actually refers to two types of endosomes, namely, the sorting endosome and the endocytic recycling compartment (ERC) (549).…”
Section: F Endocytic Recyclingmentioning
confidence: 99%
“…18 Similar study regarding leptin and glucose regulation of TRPC4 was recently published. 19 In this study, leptin is shown to activate TRPC4 channel and Ca 2C influx through TRPC4 activates AMPK that triggers translocation of ATPdependent K C channel (KATP) to the plasma membrane to hyperpolarize the resting membrane potential in pancreatic b-cell. Leptin activates TRPC4 in POMC, 20,21,22 and kisseptinsecreting hypothalamic neuron.…”
Section: Trpc4 Channelsmentioning
confidence: 99%
“…The finding of TRPC4 current in pancreatic b-cell in response to dexamethasone was interesting since similar study regarding leptin and glucose regulation of TRPC4 was recently published. 19 Leptin was first discovered in 1994 by Zang et al 59 and it is the most important and widely studied hormones in the control of energy balance. 60 Leptin is a 16 kDa protein mostly secreted from adipose tissue which has a critical role regulating body weight and energy homeostasis.…”
Section: The Roles Of Glucocorticoids and Leptin Via Trpc4 In Insulinmentioning
confidence: 99%